Time-Scale Dependent Relations Between Earth Observation Based Proxies of Vegetation Productivity - Linscheid, Nora (2022)
Much uncertainty remains in measuring the inter-annual and longer-term dynamics of vegetation gross and net primary productivity (GPP, NPP) and the connected land carbon sink. Potential for better GPP estimation lies in newer satellite products representing different processes or vegetation states, but how they capture interannual GPP dynamics remains to be explored. Here, we differentiate shorter- and longer-term vegetation dynamics and their drivers for several Earth-observation-based vegetation proxies and a GPP estimate using time series decomposition. We find that relations between proxies can significantly differ between time scales, along land cover and climate gradients. For GPP estimated at FLUXNET sites, seasonal and multiannual slopes differ by at least 25% for half of the cases investigated, indicating considerable mismatch if multiannual relations were derived from seasonal slopes. Considering time-scale-specific sensitivities between proxies of vegetation productivity may improve estimates of interannual variability in vegetation productivity.